Employment situation of dentists graduated from Universidad Nacional de Colombia workers in Private Healthcare Providing Institutions (IPS) in Bogotá (Revista Nacional de Odontología, 2020)
Introduction: Within capitalism, oral health services are considered private consumer goods and dentists are measured by their competitiveness / productivity. In Colombia, private companies have largely taken the dental services market, hiring dentists trained in the clinical-healthcare field, in business profitability and with a “commercial profile” through the labor flexibility model. The objective of this study was to describe the employment situation of dentist’s workers in Private Healthcare Providing Institutions in Bogotá.Materials and Methods: descriptive cross-sectional study; 35 dentists graduated from the Universidad Nacional de Colombia between 2011 and 2016 participated in this study. A survey was designed with 35 closed multiple-choice questions with only one answer; the survey was submitted to "Facade validation" by three experts. The results were coded and analyzed using the STATA statistical program.Results: 71.4% of the participants are hired by contract for provision of services; 20% of them have an income of less than USD 247.86 per month, with working hours from 36 to 48 hours a week. Regarding the level of training and the functions performed, 28.6% are very dissatisfied and 48.6% dissatisfied.Conclusion: the employment situation of the group of participants translates into multi-employment, linked by employment through contract for provision of service, with low incomes, long working hours, little or no guarantee of social security benefits and job instability. Working as a dentist under these conditions ends up being the only option due to the low job offer, the need for income to survive and pay debts.
Keywords: labor flexibility; dentist; job satisfaction; employment situation; job insecurity